Application of Synthetic Consortia for Improvement of Soil Fertility, Pollution Remediation, and Agricultural Productivity: A Review - Parul Chaudhary; Miao Xu; Lukman Ahamad; Anuj Chaudhary; Govind Kumar; Bartholomew Saanu Adeleke; Krishan K. Verma; Dian-Ming Hu; Ivan Širić; Pankaj Kumar; Simona M. Popescu; Sami Abou Fayssal (Agronomy, 2023)
Climate change, inadequate possessions, and land degradation all pose obstacles to modern agriculture. In the current scenario, the agriculture industry is mainly dependent on the use of chemical-based pesticides and fertilizers that impact soil health and crop productivity. Moreover, water scarcity leads farmers in drastically affected regions to use heavy metal-enriched water sources mainly originating from industrial sources for field crops irrigation. Soil pollutants can be carried into the human body via dust and water, creating negative health effects varying from simple symptoms, e.g., nausea and diarrhea and reaching death in critical cases. Thus, to clean soil contaminants, and improve soil fertility and agricultural production, alternatives to chemical fertilizers must be developed. Therefore, using beneficial microbes found in plant-associated soil microorganisms offers an effective strategy to alleviate some of these challenges, improving soil fertility, and crop yield, and protecting plants from stress conditions. Through the use of synergistic interactions, the synthetic consortium strategy seeks to improve the stability of microbial communities. In this review, synthetic consortia and their potential use in agriculture were discussed. Further, engineering new effective synthetic consortia was suggested as an effective approach in the concept of environmental bioremediation of soil pollutants and contaminants.